Social Support and Mental Health Outcomes Among U.S. Army Special Operations Personnel. Issue 6 (6th October 2016) - Russell, Dale W.; Benedek, David M.; Naifeh, James A.; Fullerton, Carol S.; Benevides, Nikki; Ursano, Robert J.; Russell, Cristel A.; Forsten, Robert D.; Cacciopo, John T.
Abstract : Mental health disorders continue to plague service members and veterans; thus, new approaches are required to help address such outcomes. The identification of risk and resilience factors for these disorders in specific populations can better inform both treatment and prevention strategies. This study focuses on a unique population of U.S. Army Special Operations personnel to assess how specific avenues of social support and personal morale are related to mental health outcomes. The results indicate that, whereas personal morale and friend support reduce the relationship between combat experiences and posttraumatic stress disorder (PTSD), strong unit support exacerbates the negative effects of combat experiences in relation to PTSD. The study thus shows that although informal social support can lessen postdeployment mental health concerns, military populations with strong internal bonds may be at greater risk of PTSD because the support that they receive from fellow service members may heighten the traumatic impact of combat experiences.